PUBLIC SPACE FUNCTION TRANSFORMATION (CASE STUDY: ENGKU PUTERI SQUARE IN BATAM CITY) - Murtiono, Hendro; Gunawan, I Gusti Ngurah Anom (Universitas Ibn Khaldun Bogor, 2022)
Engku Puteri Square is an open field which is usually called